Preservice teachers’ technological pedagogical content knowledge development: A bibliometric review - Su, Jiahong (Frontiers in Education, 2023)
Nowadays, Technological Pedagogical Content Knowledge (TPACK) has become an emerging topic in teacher education research. This review aims to analyse the global trends of the research on preservice teachers’ Technological Pedagogical Content Knowledge (TPACK) development. I used the bibliometric approach to researching preservice teachers’ TPACK by identifying the most cited publications, journals, authors, funding agencies, and keywords used in the eligible studies (N =114). The results show that preservice teachers’ TPACK research began in 2007 and the scientific community's interest in this subject has been irregular. This study presents a global perspective on preservice teacher TPACK research and provides researchers with future directions.